THE ROLE OF SOCIAL SCIENCES IN THE EDUCATION OF YOUNG PEOPLE - Mukhiddin Nazarov (Journals Park Publishing, 2022)
This article analyzes the development of modern science, its empirical and theoretical level as a means of testing technical and scientific hypotheses, it analyzes the requirements for the automation information retrieval system, mathematical methods, issues of development of a specific field of philosophical knowledge in computer science-technical philosophy.
Keywords: system; structure; element